ANALISIS STRUKTUR PASAR DAN PERILAKU INDUSTRI BAN DIINDONESIA TAHUN 2007-2011 - Lusiana . (Media Ekonomi, 2012)
Development of the tire industry in Indonesia is influenced by developmentsin the automotive industry. This occurs because the demand in tire industry is thederived demand principle for a good or service that appears as a result of thedemand for other goods. The number of motor vehicles from previous years isincreased, if in a year 2013 there was no credit restrictions so the number of motorvehicles will be growing and demand for tires in domestic will increase. This research aims to find out market structure of the tire industry in Indonesia year 2007 until 2011, and describes the conduct as a result of the existingmarket structure. Some tire companies analyzed is a company incorporated inAssociation of Tire Companies Indonesia (APBI) that is PT Goodyear Indonesia Tbk,PT Bridgestone Tire Indonesia, PT Gajah Tunggal Tbk, PT Industrial Rubber Deli,PT Sumi Rubber Indonesia, PT Eagle Premium Tyre Industry, PT SuryarayaRubberindo Industries, PT Banteng Pratama Rubber Co, PT HungA Indonesia, PTUnited KingLand and PT Surabaya Kencana Tyre Industry. The data used in thisresearch is secondary data obtained from the Association of Tire Companies Indonesia (APBI). The method of analysis used in this study is a method of structureconductperformance. To determine the market structure of the tire industry is done by calculating the concentration ratio (CR4) and Herfindal Hirschman Index (IHH).Conduct of the tire industry can be analyzed descriptively derived from interviews. The results of this research is indicate that the tire industry in Indonesiaincluding the tight oligopoly structure. This is demonstrated by the level ofconcentration ratio (CR4) of the four largest companies ranged from 87,89 to 88,81percent. While the value Herfindal Hirschman Index (IHH) ranges from 0.2669 to0.3172 percent. Four companies with the largest market share among other PTGajah Tunggal Tbk, PT Bridgestone Tire Indonesia, PT Sumi Rubber Indonesia andPT Goodyear Indonesia.Keyword: Market share, CR4, IHH, Indonesian tire industry and oligopoly.